The Role of Proline Oxidation and Metabolome Dynamics During the Flight of Bombus Impatiens - Stec, Nadia (Université d'Ottawa / University of Ottawa, 2018)
Several insect species can use the amino acid proline as a major energy substrate, a unique characteristic of these animals. Although initially thought to be limited to blood feeding dipterans, studies revealed this capability may be more widespread. Recent work showed that the bumblebee Bombus impatiens can oxidize proline at a high rate, as measured using isolated flight muscle. However, its role as a metabolic fuel to power flight is unclear. To elucidate the extent to which proline is oxidized to power flight and how its contribution changes during flight, metabolites of central carbon and proline metabolism were profiled at key time points in hemolymph and flight muscle tissue. Analysis using UPLC-MS-QTOF has revealed trends in fuel use and changes in pathway metabolites. Of 29 targeted metabolites, 18 were detected in flight muscle tissue. Two flight experiments were conducted and concentrations of metabolites at the end of prolonged flight are similar to those at rest, or have decreased significantly. In total, 14 of 19 metabolites significantly changed in concentration. The results correspond to a model of fuel use during flight, which states that proline is oxidized at the onset of flight, then carbohydrates take over as the main fuel, accompanied by a decrease in glycogen. By 8 minutes of flight, metabolite concentrations stabilize and flight performance does not change. Patterns in metabolite fluctuations suggest proline is used to supplement the Krebs cycle, and carbohydrates are the main fuel, maintained by glycogen stores. This indicates homeostatic regulation of intermediates and replenishment of fuels, or depletion of fuels due to their recruitment for ATP generation. This targeted metabolomics approach will clarify the role of proline and carbohydrate metabolism and pathway regulation during flight in B. impatiens.
Keywords: bumblebees; metabolism